Watercress (Nasturtium officinale) as a Functional Food for Non-Communicable Diseases Prevention and Management: A Narrative Review - Chikondi Maluwa; Blecious Zinan’dala; Hataichanok Chuljerm; Wason Parklak; Kanokwan Kulprachakarn (Life, 2025)
Non-communicable diseases (NCDs) such as cardiovascular disease, diabetes, cancer, and chronic respiratory conditions are the leading causes of death globally, largely driven by modifiable lifestyle factors. With growing interest in dietary strategies for NCDs prevention and management, functional foods like watercress (Nasturtium officinale) have attracted attention for their rich phytochemical content and potential health benefits. This narrative review synthesizes 88 sources published between 2019 and March 2025, exploring the effects of watercress bioactive compounds on major NCDs. Watercress is abundant in glucosinolates, isothiocyanates (especially phenethyl isothiocyanate), flavonoids, vitamins, and minerals. These compounds contribute to antioxidant, anti-inflammatory, and metabolic regulatory effects. Preclinical and clinical studies show that watercress supplementation may improve lipid profiles, reduce oxidative stress, and modulate inflammation in cardiovascular and respiratory conditions. It also appears to enhance insulin function and reduce blood glucose levels. In cancer models, watercress extracts exhibit antiproliferative, pro-apoptotic, and chemoprotective properties, with selective toxicity towards cancer cells and protective effects on normal cells. These findings highlight the therapeutic potential of watercress as a dietary adjunct in NCDs prevention and management, supporting the need for further clinical research.